THE EFFECT OF PERCEIVED RISK, SUBJECTIVE NORM, BRAND REPUTATION ON THE ATTITUDE AND THE INTENTION TO USE DIGITAL BANK SERVICES IN INDONESIA - Hartono, Nicholas Bram Yoevanto; Jaolis, Ferry; Wijaya, Serli (International Journal of Financial and Investment Studies (IJFIS), 2023)
The penetration of internet use in the world and in Indonesia has increased quite significantly in the last five years. This growth has been supported by a number of factors forming positive attitudes (the attitude toward using digital banks) and driving the intentions to adopt digital banking services (the intention to use digital banks), such as perceived risk, brand reputation, and subjective norms. Samples were purposively selected in the age range of 25-76 and the responses to the self-administered questionnaire were processed using SEM-PLS. The results of the research demonstrate that only subjective norms are able to substantially alter the attitude toward and the intentions toward using digital banks. Attitude toward using a digital bank is a key process that partially explains the influence of brand reputation and subjective norms on the intention to use a digital bank.